Formation features and the pegmatite-controlling role of the thrusts and reverse faults in the Mamskaya muscovite province - Kochnev, A. P.; Cheremnykh, A. V. (Litosfera (Ekaterinburg. Online), 2020)
Research subject. The Mamskay muscovite province (MMP) is located on the border between the Siberian platform and the Baikal orogenic area, near the boundary fault. The MMP hosts numerous regional and local thrust and reverse faults, which are typical of compression zones. This article aims to present a generalized description of the largest faults in the study area, to show their position in the regional structure of the province, as well as to consider their relationship with the main MPP tectonic stages, pegmatite and mica formation.Materials and methods. The study was conducted on the basis of literature and archive data, as well as those obtained during the authors’ long-term research. The correlation between the formation stages of the MMP reverse faults and the dynamics of the compression zone formation was investigated using the methods of physical modelling at the Laboratory for Tectonophysics, Institute of the Earth’s crust of the Siberian Branch of the Russian Academy of Sciences.Results. A comparison of experimental and field observations revealed the following six major stages in the evolution of the MMP fault tectonics: sedimentation, pre-pegmatite inversion or collisional-folded, early pegmatite, late pegmatite, post pegmatite and neotectonic. These stages were linked with the processes of folding, magmatism, pegmatite and mica formation.Conclusions. It was established that the formation of reverse faults and thrusts in the MMP resembled the process of fracturing in compression zones. The pegmatite-controlling role of the thrusts and reverse faults is determined by their age relations with the stages of the pegmatite and mica formation process. The main types of the mica-rich pegmatite fields in the MMP fault zones, which were mapped during geological survey studies, were distinguished and characterized.